Peran Faktor Psikology dan Merek pada pembelian Mobil Listrik di Pekanbaru : (Study Kasus pada Dealer Mobil Listrik XYZ Pekanbaru) - Indriaty Indriaty; Yudho Wibowo; Bayu Sedih Nanda Ria (BADAN PENERBIT STIEPARI PRESS, 2025)
The demand for electric cars in Indonesia continues to increase. This is driven by increasing environmental awareness, operational cost efficiency, and government support through incentives and policies that are pro-electric vehicles. It was recorded in Pekanbaru in December 2024 that the development of electric vehicles showed a significant increasing trend, with a growth of 150 percent. The purpose of this study was to determine the effect of psychological and brand factors on the purchase of electric cars in Pekanbaru partially or simultaneously. The research method used multiple linear regression through a nonprobability sampling technique of the accidental sampling type with a sample size of 47. The results of the study showed that there was a significant influence of psychological factors on the decision to purchase electric cars in Pekanbaru through a t-test with a p-value of 0.021. The brand variable also showed a significant influence on the decision to purchase electric cars in Pekanbaru through a t-test with a p-value of 0.044. The results of the simultaneous test proved that the psychological and brand factor variables influenced the decision to purchase electric cars in Pekanbaru through an F test with a p-value of 0.021. There is a strong positive relationship between psychological and brand factors and purchasing decisions. The results of the study also interpret that psychological and brand factors contribute to explaining purchasing decisions by 55.3% and the remaining 45.7% is explained by other factors not examined in this study.